Exploring the Influence of Citizen Journalism Content on the Malaysian Political Landscape - Nuurrianti Jalli (Kajian Malaysia, 2020)
Across the world, the use of the internet has impacted citizenship and governance which in some cases has resulted in the modification of political landscapes. Events such as the overthrow of regimes in the Middle-East during Arab Spring to the latest election upset in Malaysia in 2018, have proven the potential of new media platforms as media of change. Diverse media content generated by the public, including citizen-generated news, is shared across virtual space. Before the advent of the internet, journalism was practiced exclusively by trained journalists. These days, however, everyone has access to the tools to produce news on his or her own. This type of journalism, described in this study as citizen journalism, has changed the dynamic of news-sharing. This article seeks to explore how citizen journalism content has influenced the Malaysian political landscape. In 2016, two years before the shocking election upset in Malaysia, eight informants were interviewed for this study. The interviews were conducted in Malaysia and the United Kingdom. Despite the abundance of content on the internet generated by citizen journalists, it is believed that Malaysians in general still rely heavily on materials produced by professionals. Based on the respondents’ responses, citizen journalism does have influence over the political landscape and plays a part in shaping public opinion.